Where Have the Workers Gone since the COVID-19 Pandemic? - Ma. Christina F. Epetia; John Joseph S. Ocbina; Kimberly R. Librero (Philippine Institute for Development Studies (PIDS), 2023)
This study seeks to investigate how labor markets in the Philippines responded to the COVID-19 pandemic by decomposing the change in average annual hours of work per person and analyzing the extent of reallocation across occupations, sectors, classes of work, and nature of work. We find that the declining average hours of work before the pandemic was primarily due to the extensive margin, but the huge fall in hours of work in the first year of the pandemic was attributed to the intensive margin at a larger extent and to the extensive margin at a lesser degree. Although hours of work moderately increased later into the pandemic, the larger contribution of the change occurring at the intensive margin persisted. The same implication can be observed even when the change in average hours of work is examined by gender and age group, except for the old age bracket among women where change in average hours of work was consistently dominated by the change at the extensive margin. Furthermore, lower reallocations across occupations and sectors were seen during the pandemic, contrasting the spike in reallocations found in developed countries. That is, labor markets in the Philippines appear to be less dynamic in the face of huge economic shocks such as the COVID-19 pandemic. Although higher reallocation across classes of work can be observed for women during the pandemic, this is due to the rising employment shares of paid and unpaid family workers. Higher reallocation across nature of work also is also associated with increasing share of short-term employment. With limited social safety nets that protect worker income amid economic shocks, there appears little leeway for workers to adjust in the labor market. Workers and households should be adequately supported to protect their income and welfare, especially during economic downturns.
Keywords: 330; labor market; COVID-19 pandemic; decomposition of hours worked; reallocation index